Scaling for lobe and cleft patterns in particle-laden gravity currents - Jackson, Andrew (2014)
Lobe and cleft patterns are frequently observed at the leading edge of gravity currents, including non-Boussinesq particle-laden currents such as powder snow avalanches. Despite the importance of the instability in driving air entrainment, little is known about its origin or the mechanisms behind its development. In this work we seek to gain a better understanding of these mechanisms from a laboratory scale model of powder snow avalanches using lightweight granular material.